Impact of a Collaborative Pharmaceutical Care Service for Patients With Parkinson’s Disease - Yi, Zhan-Miao; Willis, Sarah; Zhang, Yuan; Liu, Na; Tang, Qi-Yu; Zhai, Suo-Di (Frontiers in Pharmacology, 2022)
Objective: To identify the impact of a collaborative pharmaceutical care service (CPCS) on medication safety and establish the impact of the CPCS on patient reported outcomes for Parkinson’s disease (PD) patients. Methods: Initially, PD outpatients receiving the CPCS between March 2017 and March 2019 were compared with those receiving standard of care. Pharmacist interventions data were coded to determine differences in medicines prescribed, dosage and cost savings associated with these. Following this, data of patients receiving CPCS at baseline and 3-month follow-up were collected using a questionnaire consisting of validated measures of two patient-reported outcomes (adherence and quality of life, [QoL]). Mean scores for continuous variables were calculated, with descriptive analysis of categorical variables. Change in adherence score was investigated using a Wilcoxon sign rank sum test, spearman correlation analysis was used to correlate the changes in QoL with the number of interventions, and p <0.05 indicates that the difference is statistically significant. Results: A total of 331 PD outpatients received CPCS over 490 outpatient visits with an average age of 71.83 (± 12.54). Five hundred and forty-five drug related problems were recorded as pharmacist interventions, of which most involved change to dosage (n=226, 41.47%). Compared with those receiving standard care, patients receiving CPCS were significantly less likely to have been prescribed pramipexole, more likely to have been prescribed amantadine and selegiline (all p <0.05). A lower dosages of levodopa/benserazide, levodopa/carbidopa, pramipexole and entacapone (all p <0.05) were also recorded. At baseline 122 PD outpatients with an average age of 69.93 (± 9.87) were recruited for the longitudinal study. At three-month follow-up, participants reported improvement in bodily pain subscale and medication adherence (all p<0.05). Frequency of CPCS use was related to activity of daily living subscale, the bodily pain subscale and medication adherence. Total score of PDQ-39 was associated with patient education, and usage and dosage combined with patient education, while medication adherence score was associated with usage and dosage. Conclusions: The CPCS was effective in resolving drug-related problems, and in improving patients’ medication regimens, medication adherence and QoL through patient education and dosage adjustments.